Dendronized Polymer Architectures for Fuel Cell Membranes. Issue 3 (30th April 2013) - Nielsen, M. M.; Dimitrov, I.; Takamuku, S.; Jannasch, P.; Jankova, K.; Hvilsted, S.
Abstract Multi‐step synthetic pathways to low‐ion exchange capacity (IEC) polysulfone (PSU) with sulfonic acid functionalized aliphatic dendrons and sulfonated comb‐type PSU structures are developed and investigated in a comparative study as non‐fluorinated proton exchange membrane (PEM) candidates. In each case the side chains are synthesized and introduced in their sulfonated form onto an azide‐functionalized PSU via click chemistry. Three degrees of substitution of each architecture were prepared in order to evaluate the dependence on number of sulfonated side chains. Solution cast membranes were evaluated as PEMs for use in fuel cells by proton conductivity measurements, and in the case of dendronized architectures: thermal stability. The proposed synthetic strategy facilitates exploration of a non‐fluorous system with various flexible side chains where IEC is tunable by the degree of substitution.